Stress-impaired reward pathway promotes distinct feeding behavior patterns - Fujioka, Yusuke; Kawai, Kaori; Endo, Kuniyuki; Ishibashi, Minaka; Iwade, Nobuyuki; Tuerde, Dilina; Kaibuchi, Kozo; Yamashita, Takayuki; Yamanaka, Akihiro; Katsuno, Masahisa; Watanabe, Hirohisa; Sobue, Gen; et al. (Frontiers in Neuroscience, 2024)
Although dietary behaviors are affected by neuropsychiatric disorders, various environmental conditions can have strong effects as well. We found that mice under multiple stresses, including social isolation, intermittent high-fat diet, and physical restraint, developed feeding behavior patterns characterized by a deviated bait approach (fixated feeding). All the tested stressors affected dopamine release at the nucleus accumbens (NAcc) shell and dopamine normalization reversed the feeding defects. Moreover, inhibition of dopaminergic activity in the ventral tegmental area that projects into the NAcc shell caused similar feeding pattern aberrations. Given that the deviations were not consistently accompanied by changes in the amount consumed or metabolic factors, the alterations in feeding behaviors likely reflect perturbations to a critical stress-associated pathway in the mesolimbic dopamine system. Thus, deviations in feeding behavior patterns that reflect reward system abnormalities can be sensitive biomarkers of psychosocial and physical stress.